Land Border Dispute Resolution Model in the Involvement of Customary Leaders Between Indonesia and Timor Leste in the Oecussi Enclave Area - Mangku, Dewa Gede Sudika; Yuliartini, Ni Putu Rai; Hartana; Kbarek, Lukas Norman; Monteiro, Seguito (Journal of Law and Legal Reform, 2025)
Indonesia and Timor Leste still have 4% of the land border that has not been agreed upon by the two countries, the fact is that the people who live on the border that is still being disputed have not accepted the implementation of international law which is the basis for resolving the border. However, this is precisely an obstacle when the state takes the main role, without considering the Traditional Leaders. This research will focus on efforts to reconstruct the role and existence of traditional leaders in the cultural dimension and the interconnectedness of local institutions, so that later a model for resolving state border disputes will be built with structured, legitimate cultural values that can be accepted by all components of society on the land border between the two countries, especially the Oecussi Enclave area. The outputs (products) of this research are the spectrum of the existence of traditional figures as local institutions based on religion in resolving disputes, a draft model for resolving land boundary disputes between Indonesia and Timor Leste in the Oecussi Enclave area, a draft mechanism for engineering public policies that are based on the cultural diversity of the Indonesian and Timor Leste communities, and scientific articles and intellectual property rights (IPR) on soft security based on culture in the role of traditional figures in resolving land boundary disputes between Indonesia and Timor Leste.